Vascular Endothelial Growth Factor in the Circulation in Cancer Patients May Not Be a Relevant Biomarker - Niers, Tatjana M. H.; Richel, Dick J.; Meijers, Joost C. M.; Schlingemann, Reinier O. (PloS one, 2011)
Levels of circulating vascular endothelial growth factor (VEGF) have widely been used as biomarker for angiogenic activity in cancer. For this purpose, non-standardized measurements in plasma and serum were used, without correction for artificial VEGF release by platelets activated ex vivo. We hypothesize that "true" circulating (c)VEGF levels in most cancer patients are low and unrelated to cancer load or tumour angiogenesis. We determined VEGF levels in PECT, a medium that contains platelet activation inhibitors, in citrate plasma, and in isolated platelets in 16 healthy subjects, 18 patients with metastatic non-renal cancer (non-RCC) and 12 patients with renal cell carcinoma (RCC). In non-RCC patients, circulating plasma VEGF levels were low and similar to VEGF levels in controls if platelet activation was minimized during the harvest procedure by PECT medium. In citrate plasma, VEGF levels were elevated in non-RCC patients, but this could be explained by a combination of increased platelet activation during blood harvesting, and by a two-fold increase in VEGF content of individual platelets (controls: 3.4 IU/10(6), non-RCC: 6.2 IU/10(6) platelets, p = 0.001). In contrast, cVEGF levels in RCC patients were elevated (PECT plasma: 64 pg/ml vs. 21 pg/ml, RCC vs. non-RCC, p<0.0001), and not related to platelet VEGF concentration. Our findings suggest that "true" freely cVEGF levels are not elevated in the majority of cancer patients. Previously reported elevated plasma VEGF levels in cancer appear to be due to artificial release from activated platelets, which in cancer have an increased VEGF content, during the blood harvest procedure. Only in patients with RCC, which is characterized by excessive VEGF production due to a specific genetic defect, were cVEGF levels elevated. This observation may be related to limited and selective success of anti-VEGF agents, such as bevacizumab and sorafenib, as monotherapy in RCC compared to other forms of cancer.